Penerapan Kurikulum Mandiri pada Kelas Inklusi melalui Pembelajaran Diferensiasi - Nurhidayati, Fitri; Sari, Renny Nirwana; Santoso, Agung; Hafid, Harapin; Rosyidah, Aulia (INCARE, International Journal of Educational Resources, 2024)
In implementing the independent curriculum there are various obstacles. 0ne of them is the readiness of schools and teaching staff.Differences in school conditions and students are also.To overcome them , teaching staff use the differentiation method. It is a learning method that aims to meet the needs of students according to their individual characteristics, regarding learning styles, differences in abilities and so on.Differentiation is also appropriate to apply to inclusive children.Where learning requires differences in learning methods and outcomes.This research is descriptive qualitative research with data collection methods using observation, interviews and module studies.The results of this research show that differentiation in the form of different treatment in content,process, redianess, product, also the form of learning settings and lesson modules is very appropriate to the needs of inclusive children.